The RADEC Learning Model in Primary Schools: A Systematic Literature Review - Burhanudin, Burhanudin; Maftuh, Bunyamin; Sujana, Atep; Sopandi, Wahyu; Sapriya, Sapriya; Nanola, Nouval (Universitas Pendidikan Indonesia, 2024)
The rapid development of science and technology produces consequences on the challenges that will be faced by students. Students need to develop 21st-century skills that include the ability to think critically, creatively, communicatively, and collaboratively. These skills can be obtained through the learning process, but in fact, in the field, there are still many teachers who adopt conventional learning models and tend to be teacher-centered. This kind of learning has an unfavorable impact on students' creativity, activeness, and critical thinking. This can be overcome by using the RADEC learning model. This research aims to find out the learning process that uses the RADEC model to increase student participation and student activeness in learning to foster 21st-century skills. This research uses the systematic literature review method with the PRISMA 2020 model. The 2020 prism model is used to assess the systematic review. The data collection process uses Google Scholar with a range of years 2019-2023. Data searches were carried out with the keyword Use of the RADEC Model in Elementary Schools. The results showed that 21st-century skills are crucial for students to have in facing the progress of modernization now. From the use of the RADEC model, the 21st-century skills that are improved include critical thinking, creativity, communication, and cooperation. In addition, the main challenge of RADEC model learning is if there are students who are not good at reading because the initial syntax of this model is reading. Students are required to be good at reading as an initial capital in finding information. Another challenge is that teachers must be able to analyze well related to the objectives and factors that affect the success of learning. It is hoped that this research can provide new knowledge for readers and can also be used as a reference in using the Radec learning model in schools.